2010
DOI: 10.2223/jped.2024
|View full text |Cite
|
Sign up to set email alerts
|

Advances in inhalation therapy in pediatrics

Abstract: Objectives: To review the most relevant articles regarding the technical aspects of inhalation therapy, inhalers currently available, and especially major advances in inhalation therapy in pediatrics. Sources:Articles of MEDLINE database from 1983 were reviewed, in addition to book chapters, and the most important studies were selected according to the criteria established for this article. Summary of the findings:Conventional nebulizers have a number of inconveniences, and breath-enhanced and breath-actuated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 61 publications
0
12
0
1
Order By: Relevance
“…Novolizer is a multidose DPI from MEDA. In this inhaler, a cyclone is generated in the mouthpiece through multiple supply channels during inhalation [5,11]. Newman et al (2000) reported that Novolizer ® showed a higher deposition of budesonide in the lung and lower oropharyngeal deposition when compared to Turbuhaler ® [13].…”
Section: Novolizermentioning
confidence: 99%
See 4 more Smart Citations
“…Novolizer is a multidose DPI from MEDA. In this inhaler, a cyclone is generated in the mouthpiece through multiple supply channels during inhalation [5,11]. Newman et al (2000) reported that Novolizer ® showed a higher deposition of budesonide in the lung and lower oropharyngeal deposition when compared to Turbuhaler ® [13].…”
Section: Novolizermentioning
confidence: 99%
“…The process of particle de-agglomeration can be carried out by developing technologies that use energy as key factor in DPI. Storage of energy in systems based on springs, compressed air or battery powered chambers were some of the alternatives found in inhalers [11].…”
Section: Advancements In Devicementioning
confidence: 99%
See 3 more Smart Citations